Criminal acts eradication of corruption in corporates in Indonesia - Maman Budiman (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Crime is a social phenomenon that is always faced by every society at some point in time. The existence of crime is alarming; it is also considered to disturb order and peace in society. The research method used in this study is empirical juridical, namely legal research on the enforcement or implementation of legal provisions. The results of the analysis conclude that corporations that commit criminal acts of corruption can be held criminally responsible based on doctrine and Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption Articles 1, 2 and 3 in terms of formal law. It is regulated by Supreme Court Regulation Number 13 of 2016. The factors that cause corporations to commit criminal acts of corruption are the political system, the culture of business actors, the culture of state administrators, both executive, legislative, and judicial, low legal awareness, and intense competition between one corporation and other corporations. Law enforcement officers have trouble dealing with corporations that do illegal acts of corruption because of how corporations are punished for doing illegal acts of corruption, as well as because of corporate responsibility and personal responsibility.